New Radiocarbon Dating Results from the Upper Paleolithic–Mesolithic Levels in Grotta Romanelli (Apulia, Southern Italy). Issue 5 (October 2019) - Calcagnile, Lucio; Sardella, Raffaele; Mazzini, Ilaria; Giustini, Francesca; Brilli, Mauro; D'Elia, Marisa; Braione, Eugenia; Conti, Jacopo; Mecozzi, Beniamino; Bona, Fabio; Iurino, Dawid Adam; Lembo, Giuseppe; et al.
ABSTRACT: In this paper, we present the results of the accelerator mass spectrometry radiocarbon (AMS 14 C) dating campaign performed on samples selected from different levels in Grotta Romanelli (Castro, Italy). Grotta Romanelli is one of the key sites for the chronology of Middle Pleistocene–Holocene in Mediterranean region. After the first excavation campaigns carried out in the first decades of the 1900s, the cave has been systematically re-excavated only since 2015. During the last excavation campaigns different faunal remains were selected and submitted for 14 C dating in order to confirm the chronology of the cave with a higher resolution. Isotopic ratio mass spectrometry (IRMS) measurements were also carried out on faunal remains.